The Greenland entomofauna : an identification manual of insects, spiders and their allies - Böcher, Jens; Kristensen, Niels P.; Pape, Thomas, 1960-; Vilhelmsen, Lars (Fauna entomologica Scandinavica ;, 2015)
The Greenland Entomofauna provides a richly illustrated tool for the identification of the insects, spiders, mites etc. of the country, hence enabling detailed future monitoring of range shifts of individual species.